2022
DOI: 10.1590/1516-3180.2021.0732.15092021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on compulsory notification of meningitis during the first wave of the pandemic in Brazil: an ecological study using P-score

Abstract: BACKGROUND: Meningitis is listed as one of the diseases requiring compulsory notification in Brazil. It can affect all age groups and also has no seasonality. Cases can be recorded in all months of the year and in all states of Brazil. Despite its importance, the obligation of immediate notification may have been compromised by the coronavirus disease 2019 (COVID-19) pandemic. OBJECTIVE: To analyze the immediate impact of the COVID-19 pandemic on compulsory notifications of meningitis in Brazil and its states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…In more acute pathologies such as meningitis and COVID-19, non-pharmacological measures to reduce transmissions, such as social isolation, reduction in the number of consultations, and absence of health professionals (infected by the virus), in addition to the fear of the population being assisted in hospitals and health centers, may have influenced the lower number of notifications in 2020. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In more acute pathologies such as meningitis and COVID-19, non-pharmacological measures to reduce transmissions, such as social isolation, reduction in the number of consultations, and absence of health professionals (infected by the virus), in addition to the fear of the population being assisted in hospitals and health centers, may have influenced the lower number of notifications in 2020. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In this evaluation of the measles epidemiological surveillance system in Pernambuco, we found that a system with poor timeliness will have its usefulness impaired, in terms of responding to outbreaks in a timely and standardized manner, 22 not achieving its objective of maintaining the elimination of measles through active, sensitive and appropriate surveillance. 1 ) In the case studied, centralization of laboratory diagnosis of measles at the LACEN, located in the state capital, may have contributed to poor timeliness in receiving samples, considering the operational difficulties related to transport and receipt of samples, which only takes place during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Nessa situação, impõem-se infraestruturas adequadas para os sistemas de vigilância epidemiológica e serviços de saúde, de maneira a fortalecê-los para a coleta, processamento e divulgação de dados. 20,21 Nesta avaliação do sistema de vigilância epidemiológica do sarampo em Pernambuco, observou-se que um sistema de oportunidade ruim terá sua utilidade prejudicada, no sentido de responder aos surtos em tempo hábil e de forma padronizada, 22 não alcançando seu objetivo de manter a eliminação da doença mediante uma vigilância ativa, sensível e adequada. 1 No caso estudado, a centralização do diagnóstico laboratorial do sarampo no Lacen, localizado na capital do estado, pode ter contribuído para a oportunidade ruim do recebimento das amostras, considerando-se as dificuldades operacionais relacionadas ao transporte e à recepção, esta exclusivamente diurna.…”
Section: Discussionunclassified